COVID-19 Intubation Safety: A Multidisciplinary, Rapid-Cycle Model of Improvement. (December 2020) - Tronnier, Amy; Mulcahy, Collin F.; Pierce, Ayal; Benjenk, Ivy; Sherman, Marian; Heinz, Eric R.; Honeychurch, Scott; Ho, Geoffrey; Talton, Kendarius; Yamane, David
The COVID-19 pandemic has forced the health care industry to develop dynamic protocols to maximize provider safety as aerosolizing procedures, specifically intubation, increase the risk of contracting SARS-CoV-2. The authors sought to create a quality improvement framework to ensure safe practices for intubating providers, and describe a multidisciplinary model developed at an academic tertiary care facility centered on rapid-cycle improvements and real-time gap analysis to track adherence to COVID-19 intubation safety protocols. The model included an Intubation Safety Checklist, a standardized documentation template for intubations, obtaining real-time feedback, and weekly multidisciplinary team meetings to review data and implement improvements. This study captured 68 intubations in suspected COVID-19 patients and demonstrated high personal protective equipment compliance at the institution, but also identified areas for process improvement. Overall, the authors posit that an interdisciplinary workgroup and the integration of standardized processes can be used to enhance intubation safety among providers during the COVID-19 pandemic.